2015
DOI: 10.1186/s13005-015-0075-8
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal ultrasound and postmortem histologic evaluation of tooth germs: an observational, transversal study

Abstract: IntroductionHypodontia is the most frequent developmental anomaly of the orofacial complex, and its detection in prenatal ultrasound may indicate the presence of congenital malformations, genetic syndromes and chromosomal abnormalities.To date, only a few studies have evaluated the histological relationship of human tooth germs identified by two-dimensional (2D) ultrasonography. In order to analyze whether two-dimensional ultrasonography of tooth germs may be successfully used for identifying genetic syndromes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Tooth germ sonography may, however, be applicable more broadly. Prenatal assessment of facial features via two‐dimensional ultrasound has become an important part of screening for fetal abnormalities; as oligodontia is associated with fetal pathology in a substantial number of cases, visualization of alveolar structures has been assigned a larger role in prenatal diagnostics . Of course, we recognize that under such circumstances—without prior indication of EDA gene involvement—the measures of test performance reported here will not apply, since the prior probability that the cause is a pathogenic EDA variant will be much smaller.…”
Section: Discussionmentioning
confidence: 99%
“…Tooth germ sonography may, however, be applicable more broadly. Prenatal assessment of facial features via two‐dimensional ultrasound has become an important part of screening for fetal abnormalities; as oligodontia is associated with fetal pathology in a substantial number of cases, visualization of alveolar structures has been assigned a larger role in prenatal diagnostics . Of course, we recognize that under such circumstances—without prior indication of EDA gene involvement—the measures of test performance reported here will not apply, since the prior probability that the cause is a pathogenic EDA variant will be much smaller.…”
Section: Discussionmentioning
confidence: 99%
“…The Biodentine material shows high impact upon numerous factors like absorption, strength, and density, as it contains more amount of powder with water-reducing agent and less porosity. 13 Camilleri et al in 2013 concluded Biodentine and IRM exhibited the lowest level or degree of porosity and less amount of tooth discoloration. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Such fetal findings were confirmed after birth by genetic testing. Fetal tooth germs can be visualized via ultrasound as early as 13 weeks of gestation ( 3 ), and it is customary for a healthy fetus to exhibit at least 6 dental germs in one alveolar bone ( 4 ). Recent research even suggests that ultrasonographic examination can reveal up to 10 dental germs in a healthy fetus ( 3 ).…”
Section: Discussionmentioning
confidence: 99%